IMPLEMENTASI SISTEM PEMBERIAN PESANGON TERHADAP KEMANDIRIAN PENSIUN KARYAWAN MELALUI KEWIRAUSAHAAN PADA PTPN IV REGIONAL II KEBUN AIR BATU ASAHAN SUMATERA UTARA TAHUN 2024-2025 - Yola Riska Melinda; Agustine Gloria Simbolon; Elfitri Novita Nasution; Irfan Simbolon; Patricia Herpayanti Rajaguguk; Nalom Siagian (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The internship activities were carried out with the aim of understanding the impact of the severance pay system implementation on employess’ retirement independence throught entrepreneurship at PTPN IV Regional II Air Batu Plantition, Asahan, North Sumatra, during 2024-2025. Severance pay is expected to serve as capital for employess’ entering retirement, but the suscces of its use is greatly influence by entreprenurial abilities.